Impact of cesarean section in a private health service in Brazil: indications and neonatal morbidity and mortality rates - Almeida, M A; Araujo Júnior, E; Camano, L; Peixoto, A B; Martins, W P; Mattar, R (Ceska gynekologie, 2018)
OBJECTIVE: To evaluate the incidence of, indications of, and maternal and neonatal morbidity and mortality rates in cesarean sections in a private health service in Brazil. DESIGN: Retrospective and observational study. SETTING: Private health service in Vitória, Espírito Santo, Brazil. METHODS: The patients were interviewed using a structured questionnaire to determine maternal age, gestational age at the time of delivery, number of previous deliveries, type of delivery performed, duration of labor, indications for cesarean delivery, point at which cesarean section was performed, physician responsible for delivery, and maternal morbidity, fetal morbidity, and fetal mortality rates. A descriptive analysis of the data was conducted. Students t-test was performed to compare quantitative variables, and Fishers exact test was performed for categorical variables. RESULTS: A total of 584 patients were evaluated. Of these, 91.8% (536/584) had cesarean sections, while only 8.2% (48/584) had vaginal deliveries. There were no reports of forceps-assisted vaginal deliveries. In 87.49% of the deliveries, the number of gestational weeks was more than 37. In terms of indications for performing cesarean section, 48.5% were for maternal causes, 30.41% were for fetal causes, and 17.17% were elective. Maternal re-hospitalization due to puerperal complications was necessary in 10.42% of the vaginal deliveries and in 0.93% of the cesarean deliveries (p<0.001). Complications were observed in 18.75% of the vaginally delivered newborns and in 17.16% of those delivered by cesarean section. Of the newborns with complications at birth, 40.59% (41/101) had to be admitted to the neonatal intensive care unit. There were no cases of maternal death. There were seven cases of fetal/neonatal death. CONCLUSION: We observed that the vast majority of deliveries in the private sector are performed by cesarean section, without labor, and by the patients obstetrician. We found no serious maternal complications or increased neonatal morbidity rates associated with cesarean section.
Keywords: Delivery, Obstetric; maternal complications neonatal morbidity.; Cesarean Section; Infant, Newborn, Diseases; Retrospective Studies; těhotenství; Incidence; znovupřijetí pacienta; Patient Readmission; cesarean section; Gestational Age; soukromý sektor; Brazil; incidence; Adult; mladý dospělý; perinatální mortalita; poruchy v puerperiu; Postoperative Complications; císařský řez; vedení porodu; gestační stáří; Infant, Newborn; Young Adult; ženské pohlaví; novorozenec; Puerperal Disorders; retrospektivní studie; Humans; Pregnancy; nemoci novorozenců; Brazílie; mateřská mortalita; Maternal Mortality; Perinatal Mortality; dospělí; fetální úmrtnost; Female; Fetal Mortality; Private Sector; pooperační komplikace; lidé